2020
DOI: 10.1590/1678-4685-gmb-2018-0259
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the transcriptional response to drought stress in root and leaf of common bean

Abstract: Genes related to the response to drought stress in leaf and root tissue of drought-susceptible (DS) and tolerant (DT) genotypes were characterized by RNA-Seq. In total, 54,750 transcripts, representative of 28,590 genes, were identified; of these, 1,648 were of high-fidelity (merge of 12 libraries) and described for the first time in the Andean germplasm. From the 1,239 differentially expressed genes (DEGs), 458 were identified in DT, with a predominance of genes in categories of oxidative stress, response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 118 publications
(122 reference statements)
1
19
0
Order By: Relevance
“…For the SNPs from DArTseq, the estimates of marker reproducibility (99.8%) and call rate (94%) were close and consistent with those previously reported ( Cruz et al, 2013 ; Ren et al, 2015 ), thus indicating the quality and reliability of this set of SNPs. Using the CaptureSeq, we reported the identification and genotyping of 3,166 SNPs located inside or in close proximity to 3,304 (65.42%) annotated protein-coding genes associated with drought tolerance ( Pereira et al, 2020 ) along the common bean genome. Despite a reduced number of SNPs targeted, this strategy represents a real possibility to explore the polymorphism in gene regions of interest, enabling the mapping of the set of isoforms for association analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the SNPs from DArTseq, the estimates of marker reproducibility (99.8%) and call rate (94%) were close and consistent with those previously reported ( Cruz et al, 2013 ; Ren et al, 2015 ), thus indicating the quality and reliability of this set of SNPs. Using the CaptureSeq, we reported the identification and genotyping of 3,166 SNPs located inside or in close proximity to 3,304 (65.42%) annotated protein-coding genes associated with drought tolerance ( Pereira et al, 2020 ) along the common bean genome. Despite a reduced number of SNPs targeted, this strategy represents a real possibility to explore the polymorphism in gene regions of interest, enabling the mapping of the set of isoforms for association analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A set of 5,293 differentially expressed genes under drought stress ( Pereira et al, 2020 ) were initially used as target regions of the genome. The target capture (CaptureSeq) methodology was carried out by the company RAPiD Genomics (Gainesville, FL, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of drought-related unigenes in this study were classified under different families of transcription factors (TFs) such as AP2/ERF, NAC, bZIP, DBP, MYB, HB-HD-ZIP, WRK, B3->B3, C2C2->C2C2-GATA, C3H, and bHLH, which were identified at all studied time points except for the first time point of drought stress. It was reported that TFs are considered as early activated genes that are targeted by phosphatases and PKs 63 . Among the active TFs, WRKY are largely up-regulated and known to be involved in drought stress defense pathways in plants [64][65][66] , and the members of AP2-EREBP TFs family are also shown to be highly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The expression le data indicated that PvXIP1;2 transcript levels were strongly induced by drought stress (Wu et al, 2014;Pereira et al, 2020). To verify the expression data, we performed quantitative real-time RT-qPCR using RNA isolated from drought-treated common bean, and the results con rmed the expression data (Fig.…”
Section: Expression Patterns Of Pvxip1;2mentioning
confidence: 67%